Frequency Characteristics of Rhythm Non-Assimilation in Canine Ventricular Fibrillation - M. I. Guryanov (Общая реаниматология, 2010)
Ventricular fibrillation is the main cause of sudden cardiac death in many countries, including Russia; therefore to study ventricular fibrillation is an urgent problem. Objective: to study rhythm non-assimilation in canine ventricular fibrillation. Materials and methods. The author made a frequency analysis of electrocardiograms in 25 dogs with ventricular fibrillation, by applying the fast Fourier transform method. The frequency analysis was carried out in the frequency ranges corresponding to those of delta, theta, alpha, beta, and gamma rhythms of an electroencephalogram. Results. Ventricular fibrillation is characterized by rhythm non-assimilation with the oscillations being recorded on an electrocardiogram in the frequency ranges corresponding to those of delta, theta, alpha, beta, and gamma rhythms of an electroencephalogram. The proportion of oscillations in the frequency ranges of delta, theta, alpha, beta, and gamma rhythms is determined by cardiac functional mobility (lability). The latter is reduced by ischemia in ventricular fibrillation. Diminished cardiac lability in ventricular fibrillation reflects the stages of rhythm non-assimilation with a dominant and non-dominant frequency pattern naturally detectable by the frequency analysis of an electrocardiogram in the frequency ranges of delta, theta, alpha, beta, and gamma rhythms. The greater proportion of alpha, beta, and gamma rhythm frequencies in the non-dominant frequency pattern of rhythm non-assimilation in ventricular fibrillation is, the deeper cardiac lability fall is. Conclusion. The frequency analysis of an electrocardiogram in the frequency ranges of delta, theta, alpha, beta, and gamma rhythms allows the stages of rhythm non-assimilation to be objectively determined in the entire range — at all stages of ventricular fibrillation. The findings may be included into the algorithms of an automated electrocardiogram analysis, which permits objective determination of ventricular fibrillation stages in automated defibrillators. Key words: canine heart, ventricular fibrillation, rhythm non-assimilation.